(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Sierras Pampeanas of Córdoba, Argentina, is an interesting locality to study the geochemistry of mountainous river systems, both for their socio- economic and cultural significance and for the diversity of streams and rivers that drain its slopes. Several important drainage networks in Córdoba Province have their headwaters in these ranges. In this work, the major chemical composition of water collected from four hydrological catchments is analyzed, with the aim of determining the sources of solutes, the geochemical processes that control their basin’s dynamics and the influence of climatic conditions on the seasonal variation of elemental concentrations. Four drainage basins were selected for this study. All basins are classified as 5th order in Horton’s classification (1945) (modified by Stralher, 1987) and their mean slopes vary between 5%, in the eastern flank, and more than 9% on the range’s western side. The study area is located between 31° 30’ - 32° 00’S and between 64° 30’ and 65° 10’W. Maximum altitude is about 2,400 m a.s.l. (Fig. 1). Dominant rocks are granitoids of the Achala Batholith that crop out in the upper and middle parts of the study basins, while gneisses and modern sediments dominate in the lower reaches. Climate is semiarid; mean rainfall reaches about 750 mm per year. The atmospheric input chemical signature (plu- vial and snow precipitation) was analyzed and compared with that of springs and 1st order streams (Fig. 3) using an upper continental crust (UCC, McLennan, 2001) normalized diagram. The concentration of dissolved major and trace elements is of the order of 103 to 107 times lower than the mean Upper Continental Crust. According to the observed patterns, atmospheric and spring chemical signals are very similar; however, elements such as Si, Na+ and in less importance Al+3 and Mg+2 are more enriched in springs and 1st order streams than in precipitations. The latter suggests an important contribution to water discharges in these small hydrological systems from rain/snow water stored in fractures and pores where long residence time allows silicate hydrolysis and the consequent release of more insoluble elements to the water, such as Al+3. Decreasing concentration of K+ in springs and streams is likely due to its incorporation into the illite lattice. Dissolved Ca2+ is the only major cation that keeps the atmospheric signal. In figure 4 river samples were divided according to their Horton’s order and the major ionic composition was normalized to the corresponding average values in the precipitation. As seen in the diagram, all patterns show the same trend and, as usual, elemental concentrations increase in the flow direction, evidencing solute contribution by mineral weathering. Most elements are more concentrated in superficial waters with the exception of K+, which remains associated to clay minerals, and Cl-, whose concentration keeps constant, except in 5th order rivers. Increasing elemental concentration downflow is mainly due to silicate weathering and carbonates dissolution. The latter is probably associated with atmospheric dust and disseminated calcite in regolith and soils from the study area. Mountainous rivers and streams are diluted due to the short water-rock contact time and also because soils and sediment accumulations are shallow. In the study area, total dissolved solids (TDS) vary between 10 and 60 mg l-1, which implies a shared atmospheric and weathering control (Gibbs, 1970). River waters draining crystalline rocks show electrical conductivity values from <20 to 150 µS cm-1, with a mean of 65.8 µS cm-1. On the other hand, waters in contact with unconsolidated sedimentary material show moderate electrical conductivity values (483µS cm-1). Waters are slightly acid to alkaline; with pH values that range between 5.58 and 8.80 with a mean of 7.45 ± 0.69 (mean ± SD). When rainfall water is in equilibrium with atmospheric CO2, it exhibits a pH of about 5.6 (Drever, 1997). During times of decreased rainfall, the increased concentration of atmospheric dust is responsible for the observable increased pH of rainfall, particularly during the rain events that occur at the beginning of the humid cycle (García et al., 2007; García et al., 2009). As usual, electrical conductivity increases downstream with the lowest values 18 µS cm-1, in the headwaters. Alkalinity (HCO3)- ranges between 0.058 and 2.412 meq l-1 (3.5 – 147.1 mg l-1) with a mean of 0.37 meq l-1 (22.2 mg l-1) for the whole studied area. According to their major chemical composition, rivers and streams waters are of the bicarbonate- mixed, and bicarbonate-sodium-potassium type (Piper, 1944), but some samples show no dominant anionic type. Seasonal variations of ionic concentrations were analyzed throughout the three different sampling periods. Highest concentrations were always measured under base flow conditions while the lowest were registered at maximum discharges. Elevated ionic concentrations during base discharge condition are due to the combination of several factors, principally the higher contribution of groundwater to river discharge, and in less importance the increased evapotranspiration, and increased fallout of dust accumulated in the atmosphere (aerosols). To quantify chemical weathering, a geochemical model was employed as an example of mineral and gas phases dissolved, hydrolyzed or precipitated. By means of PHREEQC 2.13 inverse modeling, the chemical weathering reactions were simulated in the study area. Two samples collected in the Panaholma river were used to run the model: one of the samples correspond to the basin´s headwaters (initial solution; 1st order, 2,179 m a.s.l.) and the other to the river’s lower reaches (in the limit of Achala granite; final solution; 5th order, 1,145 m a.s.l.). Modeling results are included in Table 2, detailed intervening phases are listed, mol l-1 H2O transferred, and percentages of each one. PHREEQC inverse models developed using water chemical data showed that: a) weathering transfers 1 mol l-1 in granitic and steep areas with semi-arid climatic conditions (e.g., Panaholma River); b) muscovite and oligoclase are the major supplier of solutes, followed by calcite, biotite and gypsum; c) illite and kaolinite (in order of importance) are the main products of weathering; d) CO2 consumption by weathering processes reaches 4 mmol kg-1 H2O; and e) CO2 accounts for nearly 40% of all the species involved in the weathering reactions occurring at the Panaholma drainage basin. All these results indicate incipient weathering, in agreement with what it is known in regions with semi arid conditions. Moreover, these results allows to infer a moderate chemical weathering rate for the whole granitic region in the Sierras de Córdoba (Argentina) and leads to extrapolate these results to other similar areas and compare them with other granitic regions.